Harangue faicte au roy par la royne mere. - Marie de Médicis, Queen, consort of Henry IV, King of France, 1573-1642 ([France?] : [publisher not identified], 1622)
"The Queen Mother warns her son of the bad influence of those who surround him in the government. She counsels Louis to listen to her advice, even though they have had their differences. Marie de Medicis simply tells her son that his realm is badly governed. One can see Richelieu in the background telling her how to approach the King"--French Political Pamphlets Digital Collection, Brigham Young University.
Signatures: A-C⁴ (last page blank).
Duvall, S.H. French Political Pamphlets Collection at the L. Tom Perry Special Collections, Harold B. Lee Library, Brigham Young University
Lindsay, R.O. French political pamphlets, 1547-1648
Also available via the World Wide Web.
Mode of access: Internet.
RBC copy: Disbound. Tears at the top of A3 and A4, affecting some text.
Keywords: Marie de Médicis, -- Queen, consort of Henry IV, King of France, -- 1573-1642.; Louis -- XIII, -- King of France, -- 1601-1643.; Marie de Médicis, -- Queen, consort of Henry IV, King of France, -- 1573-1642.; Louis -- XIII, -- King of France, -- 1601-1643.; 1610-1643; France; France -- Politics and government -- 1610-1643.; France -- History -- Louis XIII, 1610-1643 -- Pamphlets; Pamphlets -- France -- Seventeenth century (dates CE).; History